2022
DOI: 10.26554/sti.2022.7.4.427-434
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study of Structural Properties of Calcium Oxide Nanoparticles Produced by Laser-Induced Plasma and its Effect on Antibacterial Activity

Abstract: A LIBS technique was used to investigate the antibacterial activity of calcium oxide nanoparticles (CaO NPs). CaO NPs were prepared using a Q-switched Nd: YAG pulsed laser with a fundamental wavelength of 1064 nm at different energies (400-600 mJ) and constant frequency (6 Hz). A calcium powder sample was prepared after being pressed into a disc with a diameter of 1 cm. Analyzing X-ray diffraction (XRD) showed the crystalline structure of CaO NPs, crystalline size was 30.99±2 and 34.20±2.2 nm for laser energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…9). Similar antibacterial activities have been reported by several researchers for NPs (Abbas and Aadim 2022;Ahghari et al 2020;Bensy et al 2022). Ahghari et al (Ahghari et al 2020) reported antibacterial activities of NiNPs against Staphylococcus aureus and Escherichia coli.…”
Section: Antibacterial Study Antimicrobial Activities Of Nickel and C...supporting
confidence: 90%
See 1 more Smart Citation
“…9). Similar antibacterial activities have been reported by several researchers for NPs (Abbas and Aadim 2022;Ahghari et al 2020;Bensy et al 2022). Ahghari et al (Ahghari et al 2020) reported antibacterial activities of NiNPs against Staphylococcus aureus and Escherichia coli.…”
Section: Antibacterial Study Antimicrobial Activities Of Nickel and C...supporting
confidence: 90%
“…Several metal oxide nanoparticles have been reported for their potential antibacterial activities against Gramnegative and Gram-positive bacteria, consisting of Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. These metal oxide nanoparticles include Al 2 O 3 (Jawad et al 2021;Karimi et al 2021), CuO, Cu 2 O, ZnO (Asamoah et al 2020;Karuppannan et al 2021;Han et al 2022;Khosravi et al 2022), CaO (Abbas and Aadim 2022), MnO 2 , MgO (Ogunyemi et al 2020;Amrulloh et al 2021), TiO 2 (Wang et al 2020;Zhang et al 2021), Fe 3 O 4 (Azizabadi et al 2021;Kamali et al 2022), Ag 2 O (Rashidi Ranjbar et al 2020;Dharmaraj et al 2021;Mahlambi and Moloto 2022), NiO (Kannan et al 2020;Christy et al 2021), and SiO 2 (Attallah et al 2022;Tran et al 2023). The antibacterial activity lies in its physical and chemical properties, which include morphology, chemical composition, particle size, surface characteristics, solubility, crystallinity, aggregation, and crystal phase.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure, orientation, and grain size of a material may be identified by the use of XRD [19], which is a potent, non-destructive approach to material characterization. Scherer's formula was used to determine how large the individual crystals are (D) in a polycrystalline film [9,20]:…”
Section: X-ray Diffraction Analysis (Xrd)mentioning
confidence: 99%
“…This focused laser beam induces excitation and ionization of the target material, leading to the formation of a plasma plume [8]. This plume consists of a mixture of electrons, neutral atoms, and ions, which are rich in energy [9]. Subsequently, the temperature of the region involved in the process experiences rapid and significant elevation, reaching the threshold required for vaporization [10].…”
Section: Introductionmentioning
confidence: 99%